2014
DOI: 10.1093/geronb/gbu147
|View full text |Cite
|
Sign up to set email alerts
|

Grandparenthood and Subjective Well-Being: Moderating Effects of Educational Level

Abstract: Relationships with adolescent and adult grandchildren seem to generally boost positive aspects of SWB. The extent to which they may reduce negative aspects of SWB may be unequally distributed across educational groups. Less educated grandparents might be more exposed to and might be less able to cope with stressful aspects of grandparenthood than their better educated counterparts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(68 citation statements)
references
References 63 publications
2
64
0
2
Order By: Relevance
“…Their results suggest a positive relationship between caring for one's grandchildren and a variety of physical and psychological health outcomes (Arpino and Bordone 2014;Di Gessa et al 2016a, b;Hughes et al 2007;Mahne and Huxhold 2015). Moreover, focusing on the role of the relationship to grandparents in the well-being of adolescent and young adult grandchildren, Ruiz and Silverstein (2007) showed that grandchildren benefit from a close relationship to their grandparents as well, especially if they are living in a non-traditional family context.…”
Section: Intergenerational Family Relations and Healthmentioning
confidence: 96%
“…Their results suggest a positive relationship between caring for one's grandchildren and a variety of physical and psychological health outcomes (Arpino and Bordone 2014;Di Gessa et al 2016a, b;Hughes et al 2007;Mahne and Huxhold 2015). Moreover, focusing on the role of the relationship to grandparents in the well-being of adolescent and young adult grandchildren, Ruiz and Silverstein (2007) showed that grandchildren benefit from a close relationship to their grandparents as well, especially if they are living in a non-traditional family context.…”
Section: Intergenerational Family Relations and Healthmentioning
confidence: 96%
“…The non-intensive provision of childcare has been shown to be positively associated with grandparents' cognitive functioning (Arpino and Bordone, 2014), subjective wellbeing (Mahne and Huxhold, 2015), and lower risk of depression (Grundy et al, 2012). Can older adults without children or grandchildren gain similar benefits from, for instance, supporting members of their social network?…”
Section: Benefits For the Older Helper: Findings From The Behavioral mentioning
confidence: 99%
“…On the other hand, becoming a grandparent is experienced as a highly positive life transition by individuals (Mahne and Motel-Klingebiel 2012). That is, spending time with grandchildren provides emotional gratification and a sense of belonging and usefulness, with positive effects on health and life satisfaction (Arpino and Bordone 2014; Mahne and Huxhold 2015;Di Gessa et al 2016).…”
Section: Introductionmentioning
confidence: 99%